Keputusan Keuangan dan Good Corporate Governance terhadap Kinerja Dimoderasi Ukuran Perusahaan - JARIAH, AINUN (Jurnal Ilmu Manajemen Advantage, 2019)
Optimal financial performance is a company goal that can be achieved through the implementation of financial management functions. One way to improve company performance in addition to financial decisions is to implement good corporate governance. This study aims to determine the effect of financial management decisions and good corporate governance, partially or simultaneously on financial performance with the size of the company as moderating manufacturing in Indonesia. The number of samples is 37 manufacturing companies that routinely publish financial statements for the period 2014-2017. Using multiple linear regression analysis and moderation techniques, the results of the study show that partially funding decisions and good corporate governance significantly affect financial performance. Only investment decisions that have a significant partial effect on the size of the company. Investment decisions, funding decisions, dividend policies and good corporate governance simultaneously have a significant effect on both company size and financial performance. And the size of the company does not moderate the influence of financial decisions and good corporate governance on financial performance.